Status of water pollution in the coalmine of Basundhara block, Ib valley, Orissa, India - Singh, K. N.; Singh, R. K. (Journal of Nepal Geological Society, 2019)
Water pollution in coalmines has become a serious concern of everyone and with the growing demand of energy, the quest for more coal exploitation has increased. The Basundhara block of Ib valley, Orissa, India, is an opencast mine at its developing stage. Looking into the state of its progress, the coalmine water quality and its impact on organisms are discussed in this study. To reduce the health hazard from coalmine waters, necessary plant species as accumulators or absorbents are suggested in this paper.